Carolin C. Young: Apples of Gold in Settings of Silver: Stories of Dinner as a Work of Art - Jaine, Tom (Petits Propos Culinaires, 2024)
Carolin C. Young: Apples of Gold in Settings of Silver: Stories of Dinner as a Work of Art: Simon & Schuster, New York, 2002: ISBN 0743222024: 360 pp., many illus., h/b; $35.